Kassporin-KS1: A Novel Pentadecapeptide from the Skin Secretion of Kassina senegalensis: Studies on the Structure-Activity Relationships of Site-Specific “Glycine-Lysine” Motif Insertions - Yueyang Lu; Wanchen Zou; Lei Wang; Xinping Xi; Chengbang Ma; Xiaoling Chen; Tianbao Chen; Chris Shaw; Xu Zhang; Mei Zhou (Antibiotics, 2022)
Due to the abuse of traditional antibiotics and the continuous mutation of microbial resistance genes, microbial infections have become serious problems for human health. Therefore, novel antibacterial agents are urgently required, and amphibian antimicrobial peptides (AMP) are among the most interesting potential antibacterial leads. In this research, a novel peptide, named kassporin-KS1 (generically QUB-1641), with moderate antibacterial activity against Gram-positive bacteria, was discovered in the skin secretion of the Senegal running frog, Kassina senegalensis. Using site-specific sequence enrichment with a motif “glycine-lysine” that frequently occurs in ranid frog temporin peptides, a series of QUB-1641 analogues were synthesized, and effects on selected bioactivities were studied. The greatest activity enhancement was obtained when the “glycine-lysine” motif was located at the eighth and ninth position as in QUB-1570.QUB-1570 had a broader antibacterial spectrum than QUB-1641, and was eight-fold more potent. Moreover, QUB-1570 inhibited S. aureus biofilm most effectively, and significantly enhanced the viability of insect larvae infected with S. aureus. When the “glycine-lysine” motif of QUB-1570 was substituted to reduce the helix ratio and positive charge, the antibacterial activities of these synthetic analogues decreased. These data revealed that the “glycine-lysine” motif at positions 8 and 9 had the greatest enhancing effect on the antibacterial properties of QUB-1570 through increasing positive charge and helix content. This research may provide strategies for the site’s selective amino acid modification of some natural peptides to achieve the desired enhancement of activity.